Prosecution Accountability and Judicial Review - Corns, Christopher (Victoria University of Wellington Law Review, 2022)
This article examines the various ways that prosecution decisions can be challenged and, in particular, the extent to which prosecution decisions might be susceptible to judicial review. The focus is on the decision to commence or not to commence a prosecution. First considered is the extent to which that decision can be challenged pursuant to conventional criminal procedures. The availability of tort-based civil proceedings and the extent to which prosecution decisions are susceptible to judicial review are then considered. It is argued that providing adequate avenues to challenge prosecution decisions needs to be seen in the broader context of (a) the need to balance prosecutorial independence and prosecutorial accountability and (b) the separation of powers doctrine.